Analysis of Financial Ratios and Economic Condition Impact on Islamic Bank Stock Price: Study Case in Malaysia - Raisa, Carissa Aulia; Raihan, Siti; Rahmawati, Alvi; Febriyansyah, Arie; Wulan, Elis Ratna (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research is motivated by the rapid development of the Islamic capital market as a key pillar in promoting a sustainable and sharia-compliant financial system, where Islamic banking plays a dominant role in asset contribution and integration with the capital market. Despite this growth, the performance of Islamic bank stocks remains vulnerable to macroeconomic shocks such as the COVID-19 pandemic and economic slowdowns, making it crucial to understand the factors that influence them. Therefore, this study aims to analyze the influence of financial ratios and economic conditions on the stock prices of Islamic banks in Malaysia. This study uses a quantitative explanatory approach with secondary data from 2011–2023 analyzed using multiple linear regression with the help of SPSS and supported by classical assumption tests. The results show that Return on Assets (ROA) has a positive and significant effect on stock prices, confirming that profitability is a strong signal for investors, in line with signaling theory. Meanwhile, Capital Adequacy Ratio (CAR), Gross Domestic Product (GDP), and inflation showed positive and negative effects but were not significant partially, although simultaneously they had a significant effect on stock prices based on the F test. This finding indicates that internal financial performance is more dominant than macroeconomic factors in determining the stock prices of Islamic banks in Malaysia. The implication of this study is that investors should prioritize profitability indicators in decision-making, while policymakers and bank management need to improve financial performance and institutional resilience to maintain stock market stability and growth.